The issue of the information technology and technical terminology translatability from English into Russian: the typology and the nominative density levels - Bobrova , Natalia; Lebedev , Anton; Tsybina , Larisa; Pinkovetskaia , Iuliia (Journal of the University of Zulia, 2021)
The 21st century is characterized by its rapid scientific and technological advancement. Digital and technical inventions have resulted in computer globalization which caused the necessity of adequate translation of different kinds of English-language technical documentation, manuals, software products, etc. The article deals with the recent tendencies in translation and interpretation studies showing increasing interest to the ways English scientific and technical texts are rendered into Russian. The article considers the peculiarities of translating the scientific and technical vocabulary in the information technologies sphere and provides a typology of the English terms. Non-equivalent vocabulary is considered to be the most serious communication challenge. The authors identify the basic typical features of the computer discourse vocabulary, analyze the correlation between its nominal density and translatability level. The findings indicate that the ratio between the nominal density and translatability level of linguistic concepts is inversely proportional. The academic originality of the study involves the classification of technical and computer terms, as well as comparing nominal density and translatability levels. The article focuses on the most applicable English-language computer terms translation techniques, such as calquing, substantiation, generalization, semantic development, descriptive translation, antonymic translation, replacement and transformation of parts of a sentence. Pointing out that both linguistic and extralinguistic factors affect the translation solution choice, the authors believe that the correct approach to the translation process guarantees a successful intercultural communication.